Decay processes in Salix psammophila sand barriers increase soil microbial element stoichiomery ratios - Liang, Yumei; Ri, Ana; Wang, Ning (Frontiers in Environmental Science, 2022)
Salix psammophila sand barriers are a widely used engineering measure to control quicksand in northwest China. Thus, it is important to elucidate the influence of the sand barrier decay process on soil microbial ecological stoichiometric characteristics in desert environments. In the present study, field in situ sampling and laboratory index measurements were used to evaluate and compare the performance degradation, variation in soil physical and chemical properties, and soil microbial ecological stoichiometry of sand barriers during decay. The results showed that with the worsening of the decay degree, all indexes of the decay characteristics decreased significantly, among which the flexural strength of mechanical properties decreased the most, which directly led to collapse and damage. The cellulose and lignin contents of the chemical components also exhibited varying degrees of decomposition, and the soil physical and chemical properties showed a significant increase. The changes in the microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN) contents were consistent with the trend of the soil properties, and both reached their peak at 7 years. With the aggravation of decay, the stoichiometric ratios of soil microbial elements C, N, and P increased continuously. However, there was no significant increase in MBC/MBP and MBN/MBP in the early period (≤3 years) of the sand barrier establishment, but there was a significant increase in the later period (≥5 years). This indicated that S. psammophila sand barriers made desert plants or shrubs susceptible to P limitation during the process of assisting the vegetation restoration of desert ecosystems (> 5 years). Stepwise linear regression analysis showed that MBC/MBN, MBC/MBP, and MBN/MBP were mainly affected by basic density (BD), while MBC was significantly affected by dissolved organic carbon (DOC) and total nitrogen (TN), and MBN was significantly affected by TN and SOC. Therefore, the S. psammophila sand barrier changes soil properties by degrading its own chemical components during the decay process, finally increasing soil fertility and the activity of soil microorganisms, which can still be further promoted and used in the resource utilization process of mechanical sand barriers in the future.